The glory of the invisible God two powers in heaven traditions and early Christology - Orlov, Andrei A. 1960- ([London] T&T Clark, 2019)
"Andrei Orlov examines early Christological developments in the light of rabbinic references to the "two powers" in heaven, tracing the impact of this concept through both canonical and non-canonical material. Orlov begins by looking at imagery of the "two powers" in early Jewish literature, in particular the book of Daniel, and in pseudepigraphical writings. He then traces the concept through rabbinic literature and applies this directly to understanding of Christological debates. Orlov finally carries out a close examination of the "two powers" traditions in Christian literature, in particular accounts of the Transfiguration and the Baptism of Jesus. Including a comprehensive bibliography listing texts and translations, and secondary literature, this volume is a key resource in researching the development of Christology."--
Abbreviations -- Preface -- Introduction -- Part I: Two Powers in Heaven Traditions in Jewish Accounts -- Chapter 1: "Two Powers" Appearances in Early Jewish Accounts -- Chapter 2: Theophanic Molds in Rabbinic and Hekhalot Two Powers Debates -- Chapter 3: Conclusion -- Part II: Two Powers in Heaven Traditions in Early Christian Accounts -- Chapter 4: Kavod on the Mountain: The Transfiguration Account -- Chapter 5: Kavod on the River: The Baptism Account -- Chapter 6: Conclusion -- Bibliography -- Index
Abstract freely available; full-text restricted to individual document purchasers
Barrierefreier Inhalt: Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Jesus Christ -- History of doctrines; Jesus Christ; Dualism (Religion) in rabbinical literature; Dualism (Religion) -- Christianity; Rabbinical literature -- History and criticism; Biblical studies & exegesis; Electronic books